Polyphyly of Tomopterna (Amphibia: Ranidae) based on sequences of the mitochondrial 16S and 12S rRNA genes, and ecological biogeography of Malagasy relict amphibian groups - Vences, Miguel; Glaw, Frank; Kosuch, Joachim; Das, I.; Veith, Micheal (Memoires de Iα Societe de Biogeographie, 2000)
Frog s currentl y attribute d t o th e rani d genu s Tomopterna ar e know n from sub-sahara n Africa , souther n Asi a an d Madagascar . Molecula r studie s o f mitochondria l 12 S rRN A an d 16 S rRN A gen e sequence s indicat e tha t eac h o f thes e geographi c cluster s ar e mor e closel y relate d t o othe r locall y occurrin g anura n tax a tha n the y ar e t o eac h other . Th e Malagas y T. labrosa (hithert o subgenu s Laliostoma) belong s t o a monophyleti c grou p includin g Aglyptodactylus, Boophis, an d th e mantellines ; th e souther n Asia n specie s (hithert o subgenu s Sphaerotheca) appea r t o b e relate d t o ranid s o f th e genu s Limnonectes (subgenu s Feyervarya); an d mos t surprisingly , th e Africa n specie s clustere d wit h cacosternin e ranids . Thes e result s sugges t tha t th e Asia n Sphaerotheca an d th e Malagas y Laliostoma shoul d b e raise d t o generi c rank . A s a consequence , th e distributio n patter n o f Tomopterna ar e no t informativ e regardin g continenta l drif t an d biogeographi c Madagascar-Indi a relationships . Phylogeneti c dat a o n Malagas y anuran s indicat e tha t ol d evolutionar y lineage s an d relic t form s (e . g. , Laliostoma, Aglyptodactylus, Scaphiophryne) bree d mainl y i n lenti c waterbodies , an d ofte n occu r i n savanna h habitats . I n Boophis an d mantellines , evidenc e exist s tha t th e mos t basa l group s ar e rathe r generalize d pon d breeders , wherea s th e specios e group s o f fores t broo k breeder s ma y b e monophyleti c group s partl y o f mor e recen t origin . I f corroborate d b y furthe r evidence , thi s tren d woul d indicat e a n originall y relativel y dr y an d ope n habita t typ e i n Madagasca r a t th e tim e o f differentiatio n o f th e mai n lineage s o f Malagas y anurans , whic h ma y hav e take n plac e i n th e lat e Mesozoi c o r earl y Cenozoi